Differential Cross-Lagged Relations of Frailty Predicting Later Depression in Older Women Versus Men - De Moraes-Ferrari, G (SAGE Publications Ltd, 2025)
This study aimed to investigate autoregressive and lagged associations over 2 years between frailty, depression and quality of life, and to examine sex differences in these longitudinal associations among European men and women aged ≥50 years. The analyses included 10,077 individuals (5589 women) from 12 European countries. Women attested to a higher frailty and depression score and lower quality of life than men. For both sexes, frailty and depression correlated positively cross-sectionally and longitudinally (2 years later), while quality of life correlated negatively with frailty and depression cross-sectionally and longitudinally. With regard to lagged associations, for both men and women, frailty proved to be a predictor of depression 2 years later. In turn, depression did not predict frailty and quality of life 2 years later in women, but it did among men. © The Author(s) 2025
Keywords: ageing; depression; frailty; longitudinal data; quality of life